KONSTRUKSI ETIKA KOMUNIKASI EDUKATIF DALAM QS. AL-KAHFI AYAT 66: PERSPEKTIF TAFSIR ISYARI IBN ‘AJIBAH - Muhammad Fawwaz; Mohd Nazri Bin Johari; Rafil Abil Alfarisi; Hidayatullah Ismail (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This journal aims to construct the ethics of student-teacher communication from the perspective of ishari interpretation through an analysis of Surah Al-Kahf verse 66 in al-Bahr al-Madid by Ibn ‘Ajibah. The background of this study is based on the importance of communication ethics in Islamic education, which is not only oriented toward the transfer of knowledge, but also toward the formation of manners and students’ character. In the context of modern education, especially in the digital era, communication patterns have shifted and tend to neglect ethical values. Therefore, a reconstruction of communication concepts based on the Qur’an is needed. This study uses a qualitative method with a library research approach, placing al-Bahr al-Madid as the primary source and supported by classical exegesis literature and contemporary Islamic education studies. The findings show that Surah Al-Kahf verse 66 contains principles of student-teacher communication ethics, including the attitude of asking permission politely (isti’dhan), humility (tawadu’), gentleness in speech (mulatafah), an orientation of knowledge directed toward guidance (rushd), and readiness to follow the learning process (suhbah). From the perspective of ishari interpretation, these ethical values are not merely external practices, but also reflect the inner and spiritual readiness of a student in receiving knowledge. Thus, communication ethics is an integral part of Islamic education that plays an important role in creating meaningful, civilized, and character-oriented learning.